Test Content Calcium Carbonate (CaCO3) On The Shell Of The Golden Snail (Pomaceae Canaliculata) As Anticide Substance - Nida Hamidah; Lily Aprilia; Aprilia Nur Hidayah; Ika Sukmawati (Indonesian Journal of Biology Education, 2021)
Antacids are weak bases that are used to treat gastrointestinal conditions caused by increased gastric acid secretion. Calcium carbonate is a common antacid (CaCO3). As is well known, the golden snail shell is almost entirely composed of calcium carbonate. As such, we tested the calcium carbonate (CaCO3) content in the shell of the golden snail (Pomaceae canaliculata) as an antacid substance in this study. The study was conducted empirically in four stages: preparation, XRF test, XRD test, and antacid simulation test. As a result, the golden snail's shell (Pomaceae canaliculata) contains up to 50.4161 percent calcium oxide (CaO), which has the potential to be used as a starting material for calcium carbonate extraction (CaCO3). The XRD diffractogram at 500 degree celsius shows that pure CaCO3 was produced with a typical diffraction pattern at 2 theta: 26.16 degree and 27.12 degree. Additionally, it is well established that the calcium carbonate (CaCO3) found in gold snail shells can neutralize acid. However, additional research on the use of calcium carbonate in golden snail shells (Pomaceae canaliculata) as an antacid is necessary to determine the optimal dose for successful stomach acid neutralization.